Outcome of patients with cardiac resynchronisation defibrillator therapy and a follow-up of at least five years after implant (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: Cardiac resynchronisation therapy with defibrillator backup (CRT-D) is an established therapeutic option in selected heart failure patients. Data on its pronounced long-term outcome are scarce. We evaluated the long-term outcome (>5 years) of patients with the main focus on device-associated events. METHODS: Out of a prospective CRT-D registry with 219 patients, all 49 patients (22%) who survived for at least 5 years were analysed. Baseline characteristics, device associated issues (battery longevity, lead problems, phrenic nerve stimulation, infections and pacing threshold levels), implantable cardioverter-defibrillator (ICD) therapies, mortality, changes in left ventricular ejection fraction (LVEF) and improvement in New York Heart Association (NYHA) class were considered. RESULTS: The mean ± standard deviation age of the patients was 63±10 years and follow-up was 84±18 months. Seventy-eight percent were male, 73% had nonischaemic cardiomyopathy and 80% a primary prevention indication. After initially surviving 5 years, 8 patients (16%) died during further follow-up. LVEF improved from 23%±7% to 35%±13% (p-value